An application of the Element Free Galerkin Method to the analysis of quantum well structures - Machado, J. M.; Shiyou, Y.; Passaro, A.; Abe, N. M.; Yan, W.; Wang, Z. M. (World Publishing Corporation, 2000)
In order to obtain the quantum-mechanical properties of layered semicondutor structures (quantum well and superlattice structures, for instance), solutions of the Schrodinger equation should be obtained for arbitrary potential profiles. In this paper, it is shown that such problems may be also studied by the Element Free Galerkin Method.
Keywords: convergence of numerical methods; element free Galerkin method; electromagnetic fields; Schrodinger equations